“Estrategias de afrontamiento y depresión en pacientes con insuficiencia renal crónica. puyo, 2019” - González Saltos, Joseph Henry (2020)
The objective of this research was to analyze coping and depression strategies in patients with chronic renal failure at the General Puyo Hospital. The study population comprised 55 medical records of patients attending hemodialysis treatment, 21 men and 34 women, aged between 29 and 65 years; This research is documentary - bibliographic, with a cross-experimental design and a descriptive level. The technique used is the observation and as an instrument an observation sheet designed by the researchers, it contains relevant data from the medical records and results of the psychological reagents Beck's Coping Strategies Inventory and Inventory. Some of the results obtained by the tests show that 36.4% of those investigated use the desiderative thinking strategy, and 40.0% of those investigated have mild depression. According to the results obtained, a psychoeducational intervention guide was prepared for the patients that will be put into consideration to the personnel in charge of Mental Health of the institution so that it can be validated and executed.